Epidemiological trends in burden of osteoarthritis in China: an analysis from 1990 to 2021 with forecasts for 2022–2050 - Xiaofei Cao; Ruixuan Zhu; Dan Liu; Yuanyuan Cheng; Yanmin Sun; Zhipeng Huang (Frontiers in Public Health, 2025)
ObjectiveTo analyze the epidemiological trends in the burden of osteoarthritis (OA) in China from 1990 to 2021 and predict trends to 2050.MethodsThe publicly accessible modeling data derived from the Global Burden of Disease Study 2021 were employed. The annual percent change and the annual average percentage change were calculated to analyze the trend in the burden of OA. The Age-Period-Cohort (APC) model was used to analyze the age, period, and cohort effects on the incidence, prevalence, and DALYs of OA. The decomposition method was employed to analyze the changes in the burden of OA from 1990 to 2021 in China. Spearman’s correlation coefficients were used to assess correlations between the Age-Standardized Rates (ASRs) and the mean Age-Standardized prevalence from 1990 to 2021 in China. The Bayesian age-period cohort model was utilized to forecast the burden until 2050.ResultsFrom 1990 to 2021, the age-standardized incidence rate (ASIR), age-standardized prevalence rate (ASPR), and age-standardized disability-adjusted life years rate (ASDR) of OA in China all exhibited an upward trend. In 2021, the ASIR and ASPR were 554.61 per 100,000 (95% UI: 486.85–619.54) and 7,030.66 per 100,000 (95% UI: 6,211.20–7,831.69), respectively. The ASDR was 244.79 per 100,000 (95% UI: 117.30–491.91). The age-standardized rates of OA were higher among females than among males in 2021. In different age groups, the incidence rate reached its peak in the 50–54 age group for both sexes. The decomposition analysis showed that aging, population growth, and epidemiological changes were driving an increase in the disease burden of osteoarthritis in China. The increase in the ASRs of OA in China is closely linked to the rise in obesity rates. The prediction results indicated that the ASIR first increased and then decreased, while the ASPR and ASDR showed an upward trend.ConclusionIn the future, the burden of OA in China is likely to continue to grow. Greater attention should be given to females aged 50–54 years, and rational prevention and control measures should be formulated.